Analysis Of Generative AI Applications Usage By Elementary School Teacher Education Students In Supporting The Learning Process - Thatet Dirgantara; Ria Triayomi; Petrus Murwanto; Agnes Fibriana Kurniawati (Jurnal Pendidikan Rafflesia, 2026)
The penetration of generative AI (GenAI) applications in Indonesian higher education has increased significantly; however, the understanding of the multi-application usage ecosystem among pre-service elementary school teachers remains limited. This study aims to describe the usage patterns of 13 GenAI applications by Elementary School Teacher Education (PGSD) students at Universitas Katolik Musi Charitas and to understand the functions, motives, and perceived limitations in designing lesson plans. A Convergent Parallel Mixed Methods design was applied using two parallel strands: the QUAN strand utilized an online questionnaire administered to 101 students (analyzed using descriptive frequencies and percentages), and the QUAL strand employed purposive in-depth interviews with 9–13 informants, which were analyzed using thematic analysis. Integration was conducted through a joint display at the interpretation stage. ChatGPT dominated the usage (85.1%; n=86), followed by Grammarly (21.8%; n=22) and Google Bard/Gemini (10.9%; n=11). The primary purpose of usage was seeking references or additional learning resources (83.2%). Four main themes were identified: (T1) the function of GenAI in lesson plan design, (T2) motives for selecting specific applications, (T3) perceived limitations, and (T4) usage patterns of multi-application combinations with ChatGPT as the primary application. The joint display results showed a convergence between the QUAN data and QUAL findings regarding the dominance of ChatGPT, and revealed that the purpose of use reported in the questionnaire ("seeking references") refers to specific pedagogical functions in designing teaching modules.